Numeric Analysis and Impact Loading Test On Composite Pipe Glass Fiber Reinforced Epoxy Caused by Falling Object - KETUT YODI WIDNYANA (NIM 13104057), PANDE
Research Themes about composite material become popular lately, as the improving application of composite material in industry, automotive, etc. One of composite material's application in industry is composite pipe which distribute fluid (water, oil, gas, etc) from one location to another location. Composite pipe has many advantages like corrosion resistance, light weight so it is easy to install, high strength, reduce cost for maintenance, etc. Besides that advantages, composite pipe also has disadvantages like susceptible to damage by rough handling (impact damage). Because of that reason, this thesis will analyze composite pipe subjected to impact indentor with various velocity and various shape of indenter. Analysis will be conducted by numeric using finite element method software non-linear LS-DYNA. Anlysis will be focused in deformation characteristic, absorption energy, and impact force on indenter. Result from finite element will be compared with result from experiment in laboratorium. From this experiment, the result show that deformation characteristic, absorption energy, and impact force characteristic on indenter have a good agreement with result from LS-DYNA. Increased on velocity has large influence on increasing deformation and force.